Influence of Environmental, Social and Governance (ESG) on Firm Value: Literature Review - Zuli, Wahfi (BIMA Journal (Business, Management, & Accounting Journal), 2023)
This research aims to classify relevant research regarding the impact of Firm performance in Environmental, Social and Governance (ESG) on Firm value in recent years through a literature review. The research was conducted by collecting 30 articles related to the topic of ESG and Firm Value in terms of research methods and Firm characteristics. It is hoped that the results of this research can provide a reference for companies in understanding opportunities and risks and for investors to optimize investment portfolios related to the influence of ESG on Firm value.